Quality Control of Gastrodia elata by High-Performance Liquid Chromatography with Fluorescence Detection (HPLC–FLD) and Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). (23rd March 2020) - Yu, Bocheng; Li, Zhen; Wu, Jinyi; Ying, Jiamin; Tang, Yuqing; Wu, Bingchu; Tang, Chunlan; Xu, Jinyan
Abstract: A high-performance liquid chromatography with fluorescence detection (HPLC–FLD) and principal component analysis (PCA) and hierarchical cluster analysis (HCA) were developed for the quality control of Gastrodia elata . The developed protocols were successfully applied to the analysis and evaluation of 47 batches of this material from eight regions. A standard fluorescence fingerprint for G. elata was established based on 12 common peaks measured in all samples and the similarities between sample fingerprints and standard fingerprint were almost greater than 0.85. The results of PCA and HCA analysis showed that the samples from the eight regions could be classified into three groups. The correlation between the fingerprints and antioxidant activities was investigated by a stepwise regression model and Pearson correlation analysis. Gastrodigenin and parishin E were screened and validated as potential antioxidant markers of G. elata . This study provides a valuable reference for the evaluation of G. elata and other herbal medicines or their related foods.